Mass Customization of Clothes as a Concept of Individualization in Modern Design Practices - Лагода, О. М.; Гурдіна, В. В.; Пасічник, В. О. (Art and Design, 2021)
The aim of the article is to identify the characteristics and creative potential of customization in modern design activities, through which the needs for individualization of clothing at the request of consumers are widely realized. The methodological basis of the study is an integrated approach. The method of analysis and synthesis allowed the consideration of customized production as the interaction of producer and consumer, which determines the demand and competitiveness of the design product, its artistic and aesthetic value. Methods of visual-analytical and functional analysis of customized design objects provided an opportunity to establish the potential and prospects of mass customization, to justify it in terms of individualization of things as a specific consumer choice, as well as the principle of designing design objects in the learning process. It is established that, according to most scientists, customization is, first of all, individualization of the producer's relationship with the consumer. Prerequisites for its active use in the fashion industry, in particular, in design activities, are long overdue. It was found that by satisfying individual customer requests, using flexible production systems, etc., mass customization allows companies in the fashion industry to get rid of excess stocks of finished products that become obsolete too quickly, and makes it possible to make products more attractive. It is shown that the concept of "smart (savings) consumption", for which the principles of customization are extremely promising, can be successfully implemented in the process of providing educational services. The article highlights the theoretical aspects of the essence of customization as a "mass individualization" of design products. The existing principles of clothing customization are analyzed. Possibilities and types of customization in the activity of modern designers against the background of real market conditions are characterized. The potential of customizing in design in general and in the educational process of training fashion designers in particular is shown. The obtained results provide an opportunity to systematize the types, principles and techniques of customization as an experience of practical implementation of the concepts of "smart consumption", individualization and personification in clothing design.